Monitoring Global Water and Sanitation - Norman, Rachel (Cranfield University, 2013)
The process of determining outputs and outcomes plays a key role in the setting of global targets, in defining national sector policy and strategic plans and in ensuring a continuous, safe supply of affordable water. Each of these actions, are integrally linked by aggregated data sets generated through an effective monitoring and evaluation (M&E) process. This thesis examines the various components of M&E across three case studies: Global, Kenya and Uganda, including aspects such as whether roles and responsibilities are realistically assigned and whether there is a recurring set of core indicators being monitored and reported. The research has also sought to establish an evidence base of the associated costs and efficacy of use of M&E. Through purposive and snowball sampling, fieldwork was undertaken across the case studies with 85 key stakeholders. Programme, national and global level data sets were collected through structured literature reviews, document and data archive reviews, key informant and semi-structured interviews. Qualitative and quantitative data analysis methods were applied. The results demonstrate that despite having a recurring global goal and associated target, the number and variety of indicators reported against has grown over time and at each level. In turn this is placing a burden on already resource constrained countries. Regardless of the various principles of harmonization and alignment, countries are still required to manage internally and externally driven parallel systems. Whilst the research suggests the costs of M&E are escalating, the full extent of this increase remains unknown as does the extent of efficacy of use of M&E. Despite evidence that country-led M&E processes are at some level achieving their objectives, with the continuing complexities of the sector particularly around the accompanying aid architecture, M&E is not currently ‘fit for purpose’ for use in the WASH sector and is unlikely to be providing value for money.
Keywords: Fit for purpose; value for money; Kenya; Uganda